Food safety in the CGIAR: IFPRI-CGIAR Science Council roundtable on food safety - CGIAR Science Council; International Food Policy Research Institute (Science Council Secretariat, 2007)
The Science Council continues to study and support approaches which enhance the CGIAR’s scientific research agenda for the alleviation of poverty, hunger and malnutrition Food safety is an important research area that has direct or indirect relevance to a number of CGIAR’s System Priorities, especially Priorities 2A (germplasm improvement of staples), 2C (enhancing nutrient quality and safety), Priority area 3 (value addition in various commodities), and Priority 5B (research on markets). In particular, it was suggested that the CGIAR should consider undertaking research to assist poor producers to be competitive, as increasingly stringent food safety standards, such as demanded by supermarkets or for the export market, will leave the small producers out of opportunities for improving incomes...